Predictors of response of rectal cancer to neoadjuvant radiochemotherapy - McLean Smith, Fraser (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2007)
Rectal cancers staged as cT3/T4 +/- node positive routinely receive neoadjuvant radiochemotherapy (RCT) followed by total mesorectal excision (TME). By this approach tumours can be both downstaged and downsized resulting in increased rates of complete tumour resection and sphincter preservation. Oncologically, patients with tumours that demonstrate a good histological response to RCT, characterised by complete or near- complete replacement of tumour by radiation-induced fibrosis, have lower rates of local recurrence and show improved overall survival compared to those with poor response. Furthermore, a recent seminal study found improved overall outcomes in patients with a complete clinical response to RCT managed conservatively with observation alone compared to patients who underwent surgery.
Keywords: Surgery, M.D.; M.D. Trinity College Dublin